International Student Mobility and High-Skilled Migration: The Evidence - Gabriel J. Felbermayr; Isabella Reczkowski (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
Using information from the UNCTAD, we construct a new balanced panel database ofbilateral international student mobility for 150 origin countries, 23 host countries, andthe years 19702000. We match these data with information on bilateral stocks of internationalmigrants by educational attainment from census data, available for 1990 and2000. We estimate a theory-founded gravity model by conditional fixed effects PoissonPseudo Maximum Likelihood to investigate the question: To what extent do countriesthat attract foreign students benefit from an increased stock of educated foreign workers?We find that, on average, an increase of students by 10 percent increases the stockof tertiary educated workers in host countries by about 0.9 percent. That average effectis, however, entirely driven by Anglo-Saxon countries. On average, our results imply astudent retention rate of about 70 percent. These results suggest that the costs of educatingforeign students are at least partly offset by increased availability of foreign talent.
Keywords: F22; H41; I25; 330; Migration; education; international student mobility; brain drain; panel data; Poisson model; Studierende; Auslandsaufenthalt; Internationale Wanderung; Hochqualifizierte Arbeitskräfte; Internationale Arbeitsmobilität; Brain Drain; Welt